Korelasi antara konformitas dengan cyberslacking pada mahasiswa - Nurandini, Hesti; Nuryani, Reni; Lindasari, Sri Wulan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Cyberslacking is a deviant behavior that is often carried out by students regarding internet use during lectures. Internet access is used for things that have nothing to do with academics. Conformity as a form of social influence is thought to have a relationship with cyberslacking which can make individuals tend to change their attitudes, behavior and beliefs to adapt to existing norms. Purpose: To determine the relationship between conformity and cyberslacking in students. Method: Quantitative research with correlational design. Proportional stratified random sampling technique was used to take a research sample of 346 students. Data collection was carried out using a conformity scale with a reliability value of 0.764 and a cyberslacking questionnaire with a reliability value of 0.901. The correlation analysis used is Spearman's rho. Results: The level of conformity and cyberslacking of respondents was mostly in the medium category with the respective percentages being (70.8%) and (82.7%). The results of the Spearman's rho correlation test obtained a p-value of 0.003, which shows that there is a significant relationship between conformity and cyberslacking. Conclusion: There is a positive and significant relationship between conformity and cyberslacking. Increased conformity will be followed by increased cyberslacking, and vice versa. Suggestion: Future researchers can analyze the factors that strengthen the relationship between conformity and cyberslacking in students. Keywords: Conformity; Cyberslacking; Student. Pendahuluan: Cyberslacking merupakan suatu perilaku menyimpang yang sering dilakukan oleh mahasiswa terkait penggunaan internet selama perkuliahan berlangsung. Akses internet tersebut digunakan untuk hal yang tidak ada kaitannya dengan akademik. Konformitas sebagai bentuk pengaruh sosial diprediksi memiliki hubungan dengan cyberslacking yang dapat membuat individu cenderung mengubah sikap, perilaku maupun keyakinannya untuk menyesuaikan diri dengan norma yang ada. Tujuan: Untuk mengetahui hubungan antara konformitas dengan cyberslacking pada mahasiswa. Metode: Penelitian kuantitatif dengan desain korelasional. Teknik proportionated stratified random sampling digunakan untuk mengambil sampel penelitian yang berjumlah 346 mahasiswa. Data dikumpulkan menggunakan conformity scale dengan nilai reliabilitas sebesar 0.764 dan kuesioner cyberslacking dengan nilai reliabilitas sebesar 0.901. Analisis korelasi yang digunakan adalah Spearman’s rho. Hasil: Tingkat konformitas dan cyberslacking responden sebagian besar berada pada kategori sedang dengan masing-masing persentase, yaitu (70.8%) dan (82.7%). Hasil uji korelasi Spearman’s rho diperoleh p-value sebesar 0.003 yang menunjukkan hubungan signifikan antara konformitas dengan cyberslacking. Simpulan:Terdapat hubungan positif dan signifikan antara konformitas dengan cyberslacking. Peningkatan konformitas akan diikuti dengan peningkatan cyberslacking, begitu pun sebaliknya. Saran: Peneliti selanjutnya dapat menganalisis faktor-faktor yang memperkuat hubungan antara konformitas dengan cyberslacking pada mahasiswa. Kata Kunci: Cyberslacking; Konformitas; Mahasiswa.